Human Papillomavirus (HPV)-Infected Epithelial Cells and FBLN1-Positive Fibroreticular Cells Govern the Immunogenic Tumor Microenvironment in HPV-Associated Oropharyngeal Squamous Cell Carcinoma - Doeon Gu; Joonho Shim; Soo Yoon Kim; Hye Jin Kim; Da-Yong Shin; Hyun-Tae Shin; Nayeon Choi; Woong-Yang Park; Man Ki Chung; Sung Yong Choi (Clinical and Experimental Otorhinolaryngology, 2026)
Objectives. Oropharyngeal squamous cell carcinoma (OPSCC) exhibits distinct clinical behaviors according to human papillomavirus (HPV) status. HPV-associated OPSCC is typically associated with a more favorable prognosis and improved response to therapy than non-HPV–associated OPSCC; however, the underlying differences in the tumor microenvironment (TME) remain incompletely understood.Methods. To investigate cellular and molecular factors associated with improved outcomes in HPV-associated OPSCC, we performed single-cell RNA sequencing and high-resolution spatial transcriptomics on samples from two non-HPV–associated OPSCCs, five HPV-associated OPSCCs, and three normal tonsils, with a particular focus on fibroreticular cells (FRCs).Results. Four distinct FRC subsets were identified, with FBLN1-positive FRCs significantly enriched in HPV-associated OPSCC. These cells expressed SLIT2, a molecule implicated in immune cell recruitment. Spatial mapping demonstrated that FBLN1-positive FRCs were closely associated with both tumor and immune cells, suggesting a role in promoting an immunogenic TME. In addition, HPV-associated OPSCC exhibited higher levels of proliferating epithelial cells and increased expression of antigen-presentation genes than non-HPV–associated tumors.Conclusion. These findings highlight the potential role of FBLN1-positive FRCs in promoting immune activation within the TME of HPV-associated OPSCC. Enhanced antigen presentation and epithelial proliferation may facilitate tumor-immune interactions, potentially contributing to improved clinical outcomes. This study advances understanding of TME dynamics in OPSCC and may inform future therapeutic strategies.